PENGARUH PENGELOLAAN LAHAN PERTANIAN TERHADAP EROSI DAN SEDIMENTASI DI DAS GALEH KABUPATEN SEMARANG JAWA TENGAH - , FORITA DYAH ARIANTI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Human activity in the management of agricultural land tends to be dynamic and not pay attention to the environmental equilibrium. These conditions cause erosion and sedimentation. Finally, these generate environmental damage. Key words: Management, agriculture land, erosion, sediment, conservation. Erosion can be prevented to a minimum on land that has good conservation, otherwise more intensive erosion occurs on land that has a poor conservation. This research are aimed (1) to evaluate the relationship between socioeconomic factors and management of agricultural land in the Galeh watershed, (2) to assess the impact of the management of agricultural land against erosion and sedimentation in the Galeh watershed